Insight into the Microcosm of the Human Growth Hormone and Its Interactions with Polymers and Copolymers A Molecular Dynamics Perspective - Lotfi-Sousefi, Zahra (Langmuir : the ACS journal of surfaces and colloids, 2021)
Therapeutic proteins nowadays have increasingly been applied for their considerable potential in treating a wide variety of diseases. The effectiveness and potency of native therapeutic proteins are limited by various factors (e.g., stability, blood circulation time, specificity). Over the past years, a great deal of effort has been devoted to developing safe and efficient protein delivery systems. Entrapment of protein into polymeric and copolymeric matrices is common among the different types of protein-based drug formulation. However, despite the massive efforts toward developing therapeutic protein delivery in experimental studies and industrial applications, there is relatively little data on the influence of polymers and copolymers on therapeutic proteins at the atomic and molecular levels. Herein, molecular dynamics (MD) simulations are used to study the effects of biocompatible synthetic polymers including methoxy poly(ethylene glycol) (MPEG), poly(lactic acid) (PLA), and poly(lactic acid) copolymers (poly(lactic-co-glycolic acid)) PLGA and MPEG-PLA(PELA)) on the structure and dynamics of the human growth hormone (hGH), and the results are compared with previous experimental findings. Our results indicate that the hGH conformation remains stable both in pure water and in the presence of polymers, and these results are in good agreement with previous experimental data. It is shown that the MPEG chains are self-assembled and folded into a semicrystalline structure; therefore, only a small portion of the protein interacts with the polymer. The other three polymers, however, interact well with the protein and partially cover its surface. Our findings suggest that the use of these polymers for protein encapsulation has the advantage of reducing protein aggregation and thus increasing drug serum half-life. Eventually, we anticipate that the research results will expand the current knowledge about encapsulation mechanisms and the molecular interactions between hGH and the polymers